PENGARUH MODAL KERJA, TENAGA KERJA, DAN PENGALAMAN (LAMA KERJA) TERHADAP PENDAPATAN NELAYAN BAGANG TANCAP DI KABUPATEN TANAH BUMBU - Nor Amelia; Ali Wardhana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study examines the influence of  (1) the application effect of  working Capital, labor and Experiense (leght of working)  to together toward income in Wirittasi Village, Kusan Hilir Sub District, Tanah Bumbu District (2) the most dominant factor effecting the income of bagang tancap fishermen in the Villlage Wirittasi, Kusan Hilir Sub District, Tanah Bumbu District.Data collected from 41 shipowners and Bagang in Village Wirittasi, Kusan Hilir Subdistrict, Tanah Bumbu District. Multiple regression analysis with help software  SPSS is version 16.The results showed that jointly the cost factor of care, working capital, labor and experiense (leght of working) an effect on bagang tancap fishermen’s  in Wirittasi Village, Kusan Hilir Subdistrict, Tanah Bumbu District. Variable Labor (X2) is the factor that has the most dominant influence to the income of bagang tancap fishermen in the Village Wirittasi Subdistrict Kusan Hilir Tanah Bumbu District.Keyword:  Working Capital, Labor And Experiense (Leght Of Working), Income Of Fishermen Bagang Tancap